Green Snake - Hark, Tsui; Ko, Tsiu; Cheung, Maggie; Wong, Joey; Chiu Man Cheuk (Tai Seng Video, 2001)
One of Hong Kong's most popular movie makers, Tsui Hark ("A Chinese Ghost Story), pulls out all the stops - from pure cinema to gaudy schlock - in "Green Snake," his adaptation of a Chinese legend of two snake sisters trying out human forms ... Radiantly fantastical, with dry ice mists and junky costumes and a hero who walks on water, "Green Snake" stars Hong Kong glamour actresses Joey Wong and Maggie Cheung as the sexy, slinky human forms of the snakes, who have been training for hundreds of years to taste human life and passions. [www.sfgate.com]
Keywords: DVD-Video